CONTINUITY AND CHANGE IN THE NURAGIC RURAL LANDSCAPE: THE CASE OF SA OSA - Giandaniele Castangia (Traces in Time, 2011)
The archaeological findings from the prehistoric settlement of Sa Osa, located in the lower Tirso Valley, central-western Sardinia, have provided new elements to the study of the human landscape of this region of the island. In particular the evidence belonging to the nuragic phase suggests the existence of a peculiar type of productive settlement, probably seasonally occupied, related to the dynamics of the river Tirso. Ceramic and lithic findings show that a number of production and craft activities were carried out in the area. The analysis of ceramics has also revealed important changes through time, which will be discussed in the text.